Geochemistry, Sr-Nd Isotopes and Zircon U–Pb Geochronology of Intrusive Rocks: Constraint on the genesis of the Cheshmeh Khuri Cu mineralization and its link with granitoids in the Lut Block, Eastern Iran - Moghaddam, M. J. (2020)
The Cheshmeh Khuri prospecting area, part of the Tertiary volcanic-plutonic rocks in the Lut Block (central eastern Iran), comprises Middle Eocene granitoid and volcanic (with basaltic andesite to rhyolite composition) sequences that intruded pyroclastic rocks. Copper mineralization is related to the granitoid rocks. The mafic rocks occur mainly as dykes and are related to a younger magmatic activity (post-mineralization) in the area. The main hydrothermal alteration zones include quartz-sericite-pyrite ± carbonate (QSP ± C), argillic, and propylitic. Mineralization (pyrite, chalcocite, chalcopyrite, sphalerite, galena and magnetite) occurs as disseminated, stockwork and vein-type. The granitoids have features typical of high-K calk-alkaline, metaluminous, and belong to magnetite granitoid series. Primitive mantle normalized trace element spider diagrams display enrichment in LILE, such as Rb, Ba, and Cs, compared to those of HFSE. Chondrite-normalized REE plots show moderately to slightly strong LREE enriched patterns, and a negligible negative Eu anomaly. Rb-Sr whole rock–feldspar–biotite-hornblende and zircon U-Pb ages between ~44.6 and ~43.4 Ma (Middle Eocene) were obtained in granitoid samples. Initial 87Sr/86Sr ratios of granitoids range from 0.7047 to 0.7054, and their εNdi values vary from −1.1 to +0.8. Initial 87Sr/86Sr ratios of mafic rocks range from 0.7043 to 0.7047, and the εNdi values vary from +0.7 to +3.5. The whole set of geochemical data of rocks in the study area indicate an origin of the parental melts in a subduction-modified upper mantle in post-collisional extension-related zone. The primitive magmas of granitoids underwent contamination and assimilation through being exposed to the continental crust, while primitive magmas of the mafic rocks do not have relevant crustal contribution. The geochemical and radiogenic isotope data for the granitoids associated with mineralization in the Cheshmeh Khuri area in comparison with those of other prospects in the Lut Block indicate that mantle has played a crucial role in their petrogeneses and metallogeneses. Due to the crustal contamination and assimilation, the proportion of mantle component that was involved in the granitic magma shows a decrease in the Cheshmeh Khuri area. It seems that the Cheshmeh Khuri area has the lowest potential for a significant amount of Cu-Au agglomeration.